Evaluation of Difunctional Vinylcyclopropanes as Reactive Diluents for the Development of Low‐Shrinkage Composites. Issue 7 (19th April 2017) - Catel, Yohann; Fässler, Pascal; Fischer, Urs; Gorsche, Christian; Schörpf, Sebastian; Tauscher, Sven; Liska, Robert; Moszner, Norbert
Abstract : The synthesis of four new low viscosity vinylcyclopropanes is described. Photopolymerization kinetics and curing characteristics of these monomers are studied by means of photo‐differential scanning calorimeter and real‐time near‐infrared photorheology. Composites based on the newly synthesized vinylcyclopropanes exhibit significantly lower polymerization shrinkage and shrinkage stress than a corresponding dimethacrylate‐based material. Abstract : Polymerization shrinkage of dental composites remains a major concern. Free‐radically polymerizable cyclic monomers can be a conceivable alternative to methacrylates for the development of low‐shrinkage composites. In this study, the one‐step synthesis of the novel low viscosity difunctional vinylcyclopropanes1 –4 is described. Photopolymerization kinetics of these monomers are investigated by photo‐differential scanning calorimeter, using bis(4‐methoxybenzoyl)diethylgermane as photoinitiator. Real‐time near‐infrared photorheology measurements are performed to evaluate rheological behavior (i.e., time of gelation, polymerization‐induced shrinkage force) and chemical conversion (i.e., double bond conversion at the gel point, final double bond conversion) of the vinylcyclopropanes in situ. The potential of these monomers as reactive diluents in dental restorative materials is evaluated. Composites based on vinycyclopropanes1 –4 show good mechanical properties and exhibit significantly lower volumetric shrinkage and shrinkage stress than corresponding dimethacrylate‐based materials. The results indicate that such monomers are promising candidates for the replacement of commonly used low viscosity dimethacrylates such as triethylene glycol dimethacrylate in dental composites.